Experience Teaches Slowly: Non‐linear Effects of Top Management Teams' International Experience on Post‐acquisition Performance. (22nd August 2021) - Piaskowska, Dorota; Trojanowski, Grzegorz; Tharyan, Rajesh; Ray, Suparna
Abstract: Executives' international experience is commonly considered a critical asset for multinational companies. The underlying presumption is that individuals learn from international experience. We revisit this presumption and propose a conceptualization of learning from international experience that accounts for the process and challenges of such learning. We use this conceptualization to examine how the international experience of top management team (TMT) members affects firm performance following cross‐border acquisition decisions of these TMTs. Empirical analyses addressing potential endogeneity concerns show that high, but not low, levels of TMT international experience have a positive impact, and that these effects are moderated by TMT nationality diversity.